Modeling and Proposed Molecular Mechanism of Hydroxyurea Through Docking and Molecular Dynamic Simulation to Curtail the Action of Ribonucleotide Reductase - Iman, Maryam; Khansefid, Zeynab; Davood, Asghar (Recent Patents on Anti-Cancer Drug Discovery, 2016)
Background: Ribonucleotide Reductase (RNR) is an important anticancer chemotherapy target. It has main key role in DNA synthesis and cell growth. Therefore several RNR inhibitors, such as hydroxyurea, have entered the clinical trials. Based on our proposed mechanism, radical site of RNR protein reacts with hydroxyurea in which hydroxyurea is converted into its oxidized form compound III, and whereby the tyrosyl radical is converted into a normal tyrosine residue. Objective: In this study, docking and molecular dynamics simulations were used for proposed molecular mechanism of hydroxyurea in RNR inhibition as anticancer agent. Method: The binding affinity of hydroxyurea and compound III to RNR was studied by docking method. The docking study was performed for the crystal structure of human RNR with the radical scavenger Hydroxyurea and its oxidized form to inhibit the human RNR. hydroxyurea and compound III bind at the active site with Tyr-176, which are essential for free radical formation. This helps to understand the functional aspects and also aids in the development of novel inhibitors for the human RNR2. To confirm the binding mode of inhibitors, the molecular dynamics (MD) simulations were performed using GROMACS 4.5.5, based upon the docked conformation of inhibitors. Results: Both of the studied compounds stayed in the active site. The results of MD simulations confirmed the binding mode of ligands, accuracy of docking and the reliability of active conformations which were obtained by AutoDock. Conclusion: MD studies confirm our proposed mechanism in which compound III reacts with the active site residues specially Tyr-176, and inhibits the radical generation and subsequently inhibits the RNR enzyme.
Keywords: molecular dynamic